Gerakan Wakaf Kampus: Optimalisasi Gerakan Nasional Wakaf Uang (GNWU) Di Lingkungan Kampus Menuju SDGs - Qolbi, Risyda (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2021)
This article aims to design the campus waqf movement by students as generation Z—the generation that dominates the composition of the Indonesian population—to optimize GNWU in the campus environment. The method used in this article is a qualitative method with a literature study technique and is descriptive analysis. Students as agents of change, social control, moral force, and iron stock have an important role in the success of the GNWU sustainable project. This is supported by the momentum of the demographic bonus, digital bonus and awareness of giving (sharing habits) of the younger generation which is increasing significantly. The Campus Waqf Movement is a student-focused cash waqf literacy movement that is implemented in an integrated and sustainable manner. The Campus Waqf Movement seeks to optimize the potential of students in supporting GNWU which can be done by forming a waqf drive community on campus. This campus waqf driving community is oriented to the cadre of competent and quality Nazirites so that cash waqf can provide more value for benefits, especially for the campus community. The Campus Waqf Movement can be implemented by involving all elements on campus, namely students and campus parties with supervision from BWI. The Campus Waqf Movement is expected to be a pioneer in the waqf movement in the campus environment in supporting GNWU which is oriented towards achieving the 2030 SDGs. Keywords: GNWU, campus waqf movement, cash waqf, sustainability project.